Perirectal angioleiomyoma preoperatively misdiagnosed as rectal cancer: a case report - Liu, Wenhan; Wen, Xianxiong; Hu, Dongping; Ma, Hong (Frontiers in Oncology, 2024)
Angioleiomyoma (ALM) is a rare benign perivascular (pericytic) tumor primarily composed of well-differentiated smooth muscle and vascular components. Its clinical and radiological features lack specificity, making diagnosis challenging and prone to misdiagnosis. This report summarizes the clinical data of a patient treated at our hospital who was preoperatively misdiagnosed with rectal cancer but was subsequently found to have perirectal ALM. Additionally, a review of the relevant literature is provided.